2022
DOI: 10.1111/jifm.12165
|View full text |Cite
|
Sign up to set email alerts
|

Proposed international standard on auditing financial statements of less complex entities: IAASB IAAER roundtables—Breakout 2 Design, Structure, and Content

Abstract: In this commentary, we summarize stakeholder views articulated during roundtables addressing the 2021 International Auditing and Assurance Standards Board's (IAASB) Exposure Draft: Proposed International Standard on Auditing of Financial Statements of Less Complex Entities (ED LCE). In support of its mission, the International Association for Accounting Education and Research (IAAER)—together with the IAASB—organized by‐invitation roundtables bringing together audit practitioners, academics, and financial stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…To summarize, the majority of submissions (81 comment letters or 55.8%) saw potential in the new standard and one-third (39 comment letters or 26.9%) were not entirely convinced that the planned reform would be successful without modifications. These results are in line with van Nieuw Amerongen et al. ’s (2022) study, which found that 58% of the roundtable participants agreed that the ED ISA for LCEs is adequately structured regarding requirements and 11% of the roundtable participants stated that the ED needs improvements.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…To summarize, the majority of submissions (81 comment letters or 55.8%) saw potential in the new standard and one-third (39 comment letters or 26.9%) were not entirely convinced that the planned reform would be successful without modifications. These results are in line with van Nieuw Amerongen et al. ’s (2022) study, which found that 58% of the roundtable participants agreed that the ED ISA for LCEs is adequately structured regarding requirements and 11% of the roundtable participants stated that the ED needs improvements.…”
Section: Resultssupporting
confidence: 88%
“…The comment letters also discussed whether the ISA for LCEs should be a stand-alone standard; therefore, we examined the views related to the stand-alone nature in detail. This examination also enabled us to compare the results with those of van Nieuw Amerongen et al. ’s (2022) study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations